Access and utilization of maternal health services in rural Myanmar - Myo Yar Zar; Soparth Pongquan; Routray, Jayant Kumar; Chatterjee, Joyee S.; Ministry of Foreign Affairs, Norway (Pathum Thani : Asian Institute of Technology, 2016)
The research provided the understanding the ground realities of rural mothers on utilization of maternal health services (MHS) provided by Ministry of Health in Myanmar. This research was to analyze the access and utilization of rural women on MHS provided by Myanmar Government specifically on examining the awareness, accessibility, availability and affordability on MHS by rural women on MHS; assessing the utilization of MHS by rural women; analyzing the factors associated with utilization; assessing the satisfaction of and benefits gained from utilization of MHS; identifying their problems and needs; and providing the recommendations to improve access and utilization and to enhance greater benefits gained for rural mothers. This research focused on Myanmar government{u2019}s maternal health program including the provision of three components of MHS such as antenatal, delivery and postnatal cares according to the national standard components of maternal health services. ThaPhyay Khan rural health center located in Thanlyin township of Yangon region was selected as a study area due to the presence of all government health facilities on provision of all components of antenatal, delivery and postnatal care services to rural mothers. It is an evaluation research with survey design using survey questionnaire with120 sampled mothers from six villages near to and far from rural health center. Field observation, key informants interview and focus group discussions were also applied to support the quantitative analysis of the research. The main findings of the research showed that all mothers were highly aware of major components of national standard MHS. Lesser awareness of mothers on some components were found out especially in postnatal period and among the mothers staying far from rural health center. Free services and availability of health services at sub-rural health center enhanced the mothers to access the health centers regularly and utilized the major components of MHS. However, lack of public transportation and ambulatory services deterred the mothers to access the hospital in emergencies. More mothers from villages near to rural health center utilized the components of MHS during antenatal, delivery and postnatal periods compared to mothers staying far from rural health center. Inadequacy and unavailability of midwives made the mothers to utilize the some components of MHS particularly in delivery and postnatal periods. Not only awareness, some factors such as household income, sources of information, health problems, satisfaction on services were also associated with utilization. Mothers who utilized more on MHS were more satisfied with those services and gained high degree of benefits and those mothers were mothers staying near to rural health center, middle-aged mothers and mothers from medium and high-income families regardless of education and occupation. In addition to the awareness and utilization factors, mothers{u2019} satisfaction on provided services, maternal health knowledge level, multiple sources of information and health problem of mothers were associated with maternal health benefits gained by mothers from MHS.A set of recommendations were given to increase the accessibility and to enhance the utilization of MHS by rural mothers. They were focused on improvement of the maternal knowledge and awareness on the importance of three components of MHS as well as improvement of MHS provision by MHS providers during antenatal, delivery and postnatal periods.
Submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Thesis (M. Sc.) - Asian Institute of Technology, 2016
Keywords: Maternal health services -- Myanmar